2011
DOI: 10.1016/j.ajpath.2011.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of GLI1 in the Salivary Glands Results in an Altered Differentiation Program and Hyperplasia

Abstract: Hedgehog (Hh) signaling is a regulator of salivary gland morphogenesis, but its role in postnatal glands has only recently begun to be addressed. To examine the effects of deregulated Hh signaling in the salivary gland, we expressed the Hh effector protein GLI1, in salivary epithelial cells using both cytokeratin 5 and mouse mammary tumor virus (MMTV) transgenic systems. Ectopic pathway activation resulted in restrained acinar differentiation, formation of cystic lesions, and prominent appearance of ductal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…These include the WNT and NOTCH signaling pathways for SC self renewal and lineage determination (53)(54)(55)(56), ASCL3 for proliferation (57), and GSK3β for cell differentiation (58). In addition, the SC niche clearly plays an important role in the fate of SCs (59).…”
Section: Discussionmentioning
confidence: 99%
“…These include the WNT and NOTCH signaling pathways for SC self renewal and lineage determination (53)(54)(55)(56), ASCL3 for proliferation (57), and GSK3β for cell differentiation (58). In addition, the SC niche clearly plays an important role in the fate of SCs (59).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 However, transient Hh activation in salivary glands, such as overexpression of Gli1 transgene for 15 weeks and overexpression of Shh transgene for 1 week, did not result in any detectable tumor in mice. 15,34 Gene therapy for salivary gland hypofunction has several unique advantages, including easy access to most parenchymal cells via duct cannulation, the capacity to produce high amounts of protein, and tight encapsulation that minimizes concern about transgene spread. 35 We reported earlier that in wild-type mice with subcutaneous head and neck squamous cell carcinoma, the delivery of Ad-Shh to SMGs by retrograde ductal instillation efficiently activated the Hh/Gli pathway in SMGs, but did not activate the Hh/Gli pathway in tumors and did not affect the growth and response to radiotherapy of tumors, 15 indicating that local Hh activation in salivary glands will not promote the growth and radioresistance of preexisting tumors outside salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gliomas, GLI1 is highly expressed in multiple neoplasms such as small cell lung, pancreatic, stomach, and prostate cancer where its expression is in general associated with unfavorable overall patient survival (4 -8). Numerous reports have demonstrated that the sole overexpression of GLI1 is sufficient to induce transformation in vitro and in vivo (9,10). For instance, transgenic overexpression of GLI1 in epithelial cells generates hyperplastic lesions and tumor development (9,10).…”
mentioning
confidence: 99%
“…Numerous reports have demonstrated that the sole overexpression of GLI1 is sufficient to induce transformation in vitro and in vivo (9,10). For instance, transgenic overexpression of GLI1 in epithelial cells generates hyperplastic lesions and tumor development (9,10). These findings support the notion that increased expression of GLI1 is sufficient for the development of a subset of tumors.…”
mentioning
confidence: 99%